2000
DOI: 10.1046/j.1365-3040.2000.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of an apoplastic solute in the guard‐cell wall is sufficient to exert a significant effect on transpiration in Vicia faba leaflets

Abstract: , in the estimated aqueous volume of the guard-cell wall. The conclusion is that mannitol, a xenobiotic with structural similarity to sucrose, can move throughout the apoplast of a transpiring leaflet and accumulate in an osmotically significant concentration in the guard-cell wall. These data therefore provide support for a new role for sucrose as a signal metabolite that integrates essential functions of the whole leaf. In addition, the results raise questions about the physiological or experimental accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 42 publications
1
55
0
Order By: Relevance
“…Transgenic plants overexpressing hexokinase (HK, a sugar-phosphorylating enzyme involved in sugar sensing) specifically in guard cells exhibited accelerated stomatal closure induced by sugar. This observation supports the idea of photosynthesis feedback inhibition of stomatal conductance by Suc (Kelly et al, 2013) and agrees with the earlier suggestion by Outlaw and colleagues that Suc produced by mesophyll photosynthesis is loaded into the apoplast and carried to the vicinity of the guard cells, where an extracellular osmotic effect closes the stomata (Lu et al, 1995(Lu et al, , 1997Ewert et al, 2000;Outlaw and De Vlieghere-He, 2001;Kang et al, 2007). This might provide a mechanism for coordinating photosynthetic rates with transpiration.…”
Section: Role For Suc Other Than Osmoregulationsupporting
confidence: 92%
“…Transgenic plants overexpressing hexokinase (HK, a sugar-phosphorylating enzyme involved in sugar sensing) specifically in guard cells exhibited accelerated stomatal closure induced by sugar. This observation supports the idea of photosynthesis feedback inhibition of stomatal conductance by Suc (Kelly et al, 2013) and agrees with the earlier suggestion by Outlaw and colleagues that Suc produced by mesophyll photosynthesis is loaded into the apoplast and carried to the vicinity of the guard cells, where an extracellular osmotic effect closes the stomata (Lu et al, 1995(Lu et al, , 1997Ewert et al, 2000;Outlaw and De Vlieghere-He, 2001;Kang et al, 2007). This might provide a mechanism for coordinating photosynthetic rates with transpiration.…”
Section: Role For Suc Other Than Osmoregulationsupporting
confidence: 92%
“…These results suggest the need for additional carbon sources for guard cell starch metabolism, which most likely are imported from the mesophyll or are produced in guard cells prior to chlorophyll removal in the present study. These data are in line with the hypothesis that apoplastic sucrose is a source for guard cell symplastic sucrose and acts as an osmoticum for stomatal opening or replacing guard cell carbon stores (Lu et al ., ; Ewert et al ., ; Outlaw and De Vlieghere‐He, ; Stadler et al ., ). Nevertheless, we have found that guard cell photosynthesis is critical for intact guard cell turgor production.…”
Section: Discussionmentioning
confidence: 99%
“…Suc metabolism has been proposed to play a role in the longer term coordination (over the diurnal period) of A and g s (for review, see . Initially proposed by Outlaw and coworkers (Outlaw and Manchester, 1979;Lu et al, 1995Lu et al, , 1997Ewert et al, 2000;Outlaw and De Vlieghere-He, 2001;Kang et al, 2007), Suc generated by mesophyll photosynthesis is uploaded to the phloem and transported away from sources to sinks driven by transpiration (Outlaw and De Vlieghere-He, 2001). Excess Suc (when photosynthesis is high) is carried toward the stomata by the apoplast, stimulating stomatal closure either through some signaling mechanism or by acting as an osmoticum (Lu et al, 1997;Outlaw, 2003;Kang et al, 2007;Kelly et al, 2013).…”
Section: Mechanisms Of Coordination Between Stomatal Behavior and Mesmentioning
confidence: 99%